2015
DOI: 10.1149/2.0541504jes
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Temperature and Sulfate on the Pitting Corrosion of Titanium in High-Temperature Chloride Solutions

Abstract: The effects of temperature (100-230 • C) and sulfate concentration (0-0.5 mol L −1 ) on the pitting corrosion of titanium were studied in de-aerated 1 mol L −1 NaCl solution using cyclic potentiodynamic polarization (CPP) and linear-sweep thermammetry measurements. With increasing temperature, the breakdown potential E b of titanium decreased, while the repassivation potential E rp of titanium remained constant in 1 mol L −1 NaCl solution. The presence of sulfate ions shifted both the E b and E rp to higher va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…In this solution, titanium has the lowest anodic current densities, that is, the highest corrosion resistance. As reported in literature, in the presence of chlorides ions, breakdown potential several volts more positive than the free corrosion potential is necessary to initiate corrosion on titanium. Localized corrosion is caused by the migration of the ions across the passive film.…”
Section: Discussionmentioning
confidence: 94%
“…In this solution, titanium has the lowest anodic current densities, that is, the highest corrosion resistance. As reported in literature, in the presence of chlorides ions, breakdown potential several volts more positive than the free corrosion potential is necessary to initiate corrosion on titanium. Localized corrosion is caused by the migration of the ions across the passive film.…”
Section: Discussionmentioning
confidence: 94%
“…High temperatures hinder the formation of water films [34,36], in which case the electrochemical reaction is unlikely to initiate and progress. At the same time, temperature also influences the rates and mechanisms of electrochemical reactions [37,38,39]. Han and Li [35] observed that the weight gain and maximum pitting depth of LY12 Al in 1 mg/100 cm 2 Cl − increased with rising temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Controlling the localized corrosion of copper in severe environments such as desalination facilities, heat exchangers, plumbing, transformers or bearings in the oil industry, and copper corrosion due to electrolyte formation on electronic components or local chloride accumulation in building materials (or atmospheric corrosion) has attracted a lot of attention [ 5 , 6 , 7 , 8 , 9 ]. Titanium, because of its higher corrosion resistance and better mechanical properties in comparison with copper, has proven to be a good candidate to be joined with copper for better corrosion performance [ 10 ]. The superior corrosion resistance of Ti compared to Cu is related to the chemically unreactive, condensed and adherent oxide films formed on its surface [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Titanium, because of its higher corrosion resistance and better mechanical properties in comparison with copper, has proven to be a good candidate to be joined with copper for better corrosion performance [ 10 ]. The superior corrosion resistance of Ti compared to Cu is related to the chemically unreactive, condensed and adherent oxide films formed on its surface [ 10 , 11 ]. In fact, Ti-Cu bimetals, which combine the properties of both Ti and Cu, meet multiple necessities in terms of high thermal strength, good corrosion resistance, and high thermal and electrical conductivities for specific applications [ 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%